GENETICS OF CUMULATIVE MEASURE OF PHYSIOLOGICAL DYSREGULATION: EVIDENCE FROM LONG LIFE FAMILY STUDY. (11th November 2018) - Arbeev, K; Bagley, O; Ukraintseva, S V; Thyagarajan, B; Zmuda, J M; Lee, J H; Christensen, K; Yashin, A I
Abstract: The distance measure (DM) is a potential statistical approach to construct composite measures of physiological dysregulation based on multiple biomarkers. We constructed a DM using blood and other biomarker measures from two visits in the Long Life Family Study, with sex-specific means and variance-covariance matrices of individuals <60 years at baseline representing the "reference" population. We found that an increase in DM is associated with higher mortality risk (HR=1.22; 95% C.I.: [1.17, 1.27]), even after adjustment for a cumulative measure summarizing 85 deficits (disabilities, diseases, less severe symptoms). Our findings provide evidence that dynamics of DM represents an additional important predictor for mortality among older adults. We will discuss results of our ongoing genome-wide association studies of "static" (baseline value) and "dynamic" (slopes) characteristics of DM evaluated using joint models of longitudinal measurements of DM and mortality data which will illustrate genetic determinants of such measures.